Answer :

First term from end a = 49

t_{n} = – 11

t_{n – 1} = – 8

Common difference d = t_{n} – t_{n – 1} = – 11 – ( – 8) = – 11 + 8 = – 3

Now, By using n^{th} term of an A.P. formula

t_{n} = a + (n – 1)d

where n = no. of terms

a = first term

d = common difference

t_{n} = n^{th} terms

no. of terms n = 4

⇒ t_{4} = 49 + (4 – 1) × ( – 3)

⇒ t_{4} = 49 + 3 × ( – 3)

⇒ t_{4} = 49 – 9 = 40

Rate this question :

Attempt any threeMaharashtra Board - Algebra Papers

Attempt any four Maharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

Attempt any threeMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

Attempt any threeMaharashtra Board - Algebra Papers

Attempt any four Maharashtra Board - Algebra Papers